Multi-endpoint toxicological assessment of polystyrene nano- and microparticles in different biological models in vitro. (December 2019) - Hesler, Michelle; Aengenheister, Leonie; Ellinger, Bernhard; Drexel, Roland; Straskraba, Susanne; Jost, Carsten; Wagner, Sylvia; Meier, Florian; von Briesen, Hagen; Büchel, Claudia; Wick, Peter; Buerki-Thurnherr, Tina; et al.
Abstract: Nanoplastics (NP) and microplastics (MP) accumulate in our environment as a consequence of the massive consumption of plastics. Huge knowledge-gaps exist regarding uptake and fate of plastic particles in micro- and nano-dimensions in humans as well as on their impact on human health. This study investigated the transport and effects of 50 nm and 0.5 μm COOH-modified polystyrene (PS) particles, as representatives for NP and MP, in different biological models in vitro . Acute toxicity and potential translocation of the particles were studied at the human intestinal and placental barrier using advanced in vitro co-culture models. Furthermore, embryotoxicity and genotoxicity were investigated as highly sensitive endpoints. Polystyrene was not acutely toxic in both sizes (nano- and microparticles). No transport across the intestinal and placental barrier but a cellular uptake and intracellular accumulation of PS nano- and microparticles were determined. The particles were identified as weak embryotoxic and non-genotoxic. In contrast to single-organ studies, this multi-endpoint study is providing a data-set with the exact same type of particles to compare organ-specific outcomes. Our study clearly shows the need to investigate other types of plastics as well as towards long-term or chronic effects of plastic particles in different biological models in vitro . Graphical abstract: Unlabelled Image Highlights: Polystyrene nano- and microparticles were investigated in vitro regarding their toxicity in several biological models Polystyrene was not acutely cytotoxic in both sizes and did not induce damages on DNA No significant transport across the intestinal and placental barrier but intercellular distribution was observed This multi-endpoint study is providing a data-set with the exact same type of particles to compare organ-specific outcomes